2020
DOI: 10.1007/s10741-020-10037-x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of COVID-19-induced heart failure: a short review

Abstract: The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) that causes coronavirus disease 2019 (COVID-19) has infected more than 42.5 million people globally resulting in the death of over 1.15 million subjects. It has inflicted severe public health and economic hardships across the world. In addition to acute respiratory distress syndrome, respiratory failure, sepsis, and acute kidney injury, COVID-19 also causes heart failure (HF). COVID-19-induced HF is manifested via different mechanisms, including,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 41 publications
0
45
0
1
Order By: Relevance
“…Studies have shown that sarcomere disruption and fragmentation, enucleation, transcriptional changes, and an intense local immune response occurs in cardiomyocytes infected by SARS-CoV-2 9192. Pathological responses to acute cardiac injury and viral myocarditis, such as endothelial damage and microthrombosis, can lead to the development of coagulopathy,93 while chronic hypoxia and an increase in pulmonary arterial pressure and ventricular strain may further precipitate the incidence of cardiac injury in people who have had covid-19 94. Furthermore, sustained immune activation can lead to fibrotic changes95 and displacement of desmosomal proteins,96 which could be arrhythmogenic.…”
Section: Symptomsmentioning
confidence: 99%
“…Studies have shown that sarcomere disruption and fragmentation, enucleation, transcriptional changes, and an intense local immune response occurs in cardiomyocytes infected by SARS-CoV-2 9192. Pathological responses to acute cardiac injury and viral myocarditis, such as endothelial damage and microthrombosis, can lead to the development of coagulopathy,93 while chronic hypoxia and an increase in pulmonary arterial pressure and ventricular strain may further precipitate the incidence of cardiac injury in people who have had covid-19 94. Furthermore, sustained immune activation can lead to fibrotic changes95 and displacement of desmosomal proteins,96 which could be arrhythmogenic.…”
Section: Symptomsmentioning
confidence: 99%
“…The association between COVID-19 infection and HF has been increasingly demonstrated in the last few months, [ 40 ]. It is currently known that myocarditis, endothelial damage, coagulopathies and respiratory failure can be considered as possible risk factors for the onset of HF in severe COVID-19 patients [ [40] , [41] , [42] ].…”
Section: Cardiovascular Disease Is a Common Complication In Covid-19 mentioning
confidence: 99%
“…The tropism exhibited by the SARS-CoV-2 virus towards cardiac tissues due to several aforementioned SARS-CoV-2 receptors on the cardiac system, especially on cardiomyocytes and pericytes, could culminate in cardiac injuries, where the virus directly invades into the myocardial cells by binding to the ACE2 receptor to cause myocardial injuries. In addition to this, the bystander effect plays a significant role in mediating cardiac injuries, which include (a) systemic hyper responsiveness due to cytokine storm; (b) cardiac tissue hypoxia due to respiratory failure; (c) coronary plaque destabilization, (d) induction of coronary thrombosis, which are elicited by high SARS-CoV-2 load, are also responsible for cardiac muscle dysfunction and injuries, causing acute or fulminant myocarditis [ 28 , 29 ]. Though direct cardiac injury mediated by SARS-CoV-2 virus is not completely understood, it was evident that this virus does replicate inside cardiomyocytes and are localized at the perinuclear region of the cytoplasm, causing viral-mediated cytopathic effects, including apoptosis which was reflected by the cleaved caspase-3 expression and cessation of beating in 72 h post-infection, as demonstrated by beat rate contractility analysis [ 30 ].…”
Section: Sars-cov-2 and Its Receptors In Cardiac Pathophysiologymentioning
confidence: 99%